2015
DOI: 10.1152/jn.00666.2015
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-induced up states in the dorsal pallium of a weakly electric fish

Abstract: Elliott SB, Maler L. Stimulus-induced up states in the dorsal pallium of a weakly electric fish. J Neurophysiol 114: [2071][2072][2073][2074][2075][2076] 2015.First published August 5, 2015; doi:10.1152/jn.00666.2015.-We investigated the response of putative novelty-detecting neurons in the pallium of an electric fish to electrosensory and acoustic stimuli. Extracellular and whole cell patch recordings were made from neurons in the dorsal pallial nucleus (DD) of Apteronotus leptorhynchus. DD neurons were typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Given that DL is essential for spatial learning in goldfish (see above), we propose that DL and DD are involved in pattern separation/completion. We have shown that DDi/DDmg found neurons that could enter a sustained Up state after repeated stimulus presentations; these Up states appeared to be driven by synaptic input (Elliott and Maler, ). We hypothesize that the Up state is due to reverberatory activity within the multiple loops of the DDi recurrent network and the slow NMDA receptor EPSPs (Harvey‐Girard et al, ) which last longer than the maximum loop delay time (50 ms).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that DL is essential for spatial learning in goldfish (see above), we propose that DL and DD are involved in pattern separation/completion. We have shown that DDi/DDmg found neurons that could enter a sustained Up state after repeated stimulus presentations; these Up states appeared to be driven by synaptic input (Elliott and Maler, ). We hypothesize that the Up state is due to reverberatory activity within the multiple loops of the DDi recurrent network and the slow NMDA receptor EPSPs (Harvey‐Girard et al, ) which last longer than the maximum loop delay time (50 ms).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our work we predict that, when the fish receives social stimulation, the DC2 (DD?) region will show very strong increases in Egr‐1 mRNA expression (Harvey‐Girard et al, 2011) as well as a specific electrophysiological response—induction of Up states (Elliott and Maler, ). We believe that A. burtoni is an outstanding system to investigate the neural bases of social learning and, in particular, the interactions of DD and DL in such learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, a recent study has shown that the recurrent networks of the gymnotiform telencephalon can be induced to switch between up and down states (Elliott and Maler, 2015). Furthermore, work in zebrafish suggests that the orexin and galanin peptidergic systems of the hypothalamus can control the probability of such switches (Prober et al, 2006; Woods et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…Is it mediated only through neuromodulation, as suggested by the induced up states of the telencephalon (Elliott and Maler, 2015), or is there a more direct pathway interacting with the inferred attractor dynamics? In other words, one might want to eventually include closed loop features, going beyond the open-loop perspective that underlies the work presented here, to gain a better understanding of how behavioral state transitions occur in more complex settings.…”
Section: Discussionmentioning
confidence: 99%